Efficacy Of Spinal Anesthesia Versus General Anesthesia for Single-Level Microdiscectomy at POF Hospital, Wah Cantt: Spinal Versus General Anesthesia for Single-Level Microdiscectomy - Ali, Haris; Alam, Mehboob; Ahmad, Sohail (Pakistan Journal of Health Sciences, 2026)
Existing studies show varying results regarding the outcomes of single-level lumbar microdiscectomy under spinal anesthesia and general anesthesia, leaving uncertainty about their relative benefits. Objective: To compare the outcomes of spinal anesthesia versus general anesthesia in single-level microdiscectomy. Methods: This quasi-experimental study was conducted at the Department of Neurosurgery, POF Hospital, Wah Cantt. A total of 60 male and female patients with lumbar disc herniation with single-level microdiscectomy under spinal and general anesthesia were compared for outcomes in terms of surgery time, post-anesthesia care unit time, intraoperative blood loss, dural tear, post-operative pain, and hospital stay. Results: The mean age of the participants was 49.65 ± 7.43 years, and participants aged more than 45 years were 37 (61.7%), while the majority of the patients were female, n=32 (53.3%). The mean operative time with spinal anesthesia was 71.0 ± 4.30 minutes versus 88.00 ± 4.21 minutes with GA (p<0.001). Mean PACU time spent by patients with spinal and general anesthesia was 1.50±0.63 days and 2.03 ± 0.85 days, respectively (p=0.008). Mean hospital stay of patients with spinal was 2.57 ± 0.63 days versus 3.67 ± 0.80 days with general anesthesia (p<0.001). Dural tears were observed in patients (3.3%) with spinal versus 02 patients (6.6%) with general anesthesia (p=0.643). Conclusions: Spinal anesthesia was associated with better perioperative outcomes than general anesthesia in patients who underwent lumbar microdiscectomy when assessed in terms of operative time, PACU time, and hospital stay.